2008
DOI: 10.1186/1755-8794-1-13
|View full text |Cite
|
Sign up to set email alerts
|

The gene expression profiles of primary and metastatic melanoma yields a transition point of tumor progression and metastasis

Abstract: Background: The process of malignant transformation, progression and metastasis of melanoma is poorly understood. Gene expression profiling of human cancer has allowed for a unique insight into the genes that are involved in these processes. Thus, we have attempted to utilize this approach through the analysis of a series of primary, non-metastatic cutaneous tumors and metastatic melanoma samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
437
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(470 citation statements)
references
References 54 publications
32
437
0
1
Order By: Relevance
“…It has also been seen to protect against growth factor withdrawal-induced apoptosis in myeloid precursor cells, and surprisingly to allow differentiation of these cells, whereas Bcl-2 had an anti-proliferative function 388 . Bfl-1 is also seen overexpressed in solid tumours, such as stomach cancer 369 , breast cancer 389 , and metastatic melanoma 368 . It also appears to regulate hypoxia-induced apoptosis and oxidant-induced necrosis of epithelial cells in culture 390 , presenting an opportunity for drug studies targeting Bfl-1 in hyperoxic acute lung injury (HALI) in addition to haematological malignancies and solid tumours.…”
Section: The Role Of Bfl-1 In Cancermentioning
confidence: 99%
“…It has also been seen to protect against growth factor withdrawal-induced apoptosis in myeloid precursor cells, and surprisingly to allow differentiation of these cells, whereas Bcl-2 had an anti-proliferative function 388 . Bfl-1 is also seen overexpressed in solid tumours, such as stomach cancer 369 , breast cancer 389 , and metastatic melanoma 368 . It also appears to regulate hypoxia-induced apoptosis and oxidant-induced necrosis of epithelial cells in culture 390 , presenting an opportunity for drug studies targeting Bfl-1 in hyperoxic acute lung injury (HALI) in addition to haematological malignancies and solid tumours.…”
Section: The Role Of Bfl-1 In Cancermentioning
confidence: 99%
“…The gene encoding human Gpr19 resides on the short arm of chromosome 12 in a region that is frequently rearranged in childhood leukemia and to a lesser extent in other neoplasms; accordingly, GPR19 has been postulated to play a role in cancer development (39). In fact, high levels of mRNA coding for GPR19 were found in metastatic melanoma (7,40). Here we showed that GPR19 is associated with lung cancer.…”
Section: Discussionmentioning
confidence: 60%
“…Previous gene expression studies of melanocytic tumors also reported that the predominant change was decreased expression of genes in advanced malignancy. 14,15 Among genes that were decreased (Table 2b), SFN showed the greatest and most significant decrease. Stratifin is a protein that was initially identified in keratinizing stratified squamous epithelium and has a regulatory role in the G2/M cell cycle check point and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…However, several prior studies of gene expression have reported downregulation of keratinocyte-related proteins, such as keratins, associated with melanoma. [14][15][16] Others have encountered an increase in keratin genes in advanced melanoma. 23 Unexpectedly high expression of keratin-associated proteins in primary/early stage melanomas relative to metastases has been a matter of considerable concern to previous investigators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation